Synthesis and Adsorption-Photocatalytic Properties of ZnO/Biochar Composites - Jaroniec, Jerzy; Balogh, Ilknur (Journal of Green Energy and Environmental Engineering, 2024)
This study designed and constructed novel ZnO/NOC-based composite photocatalytic materials (ZnO/NOC, Cu@ZnO/NOC, Sn@ZnO/NOC) by leveraging the advantages of biochar, such as its large specific surface area and abundant pore structure. Various advanced characterization techniques were employed to investigate the synergistic effects between components, microstructure, electrical conductivity, and optical properties of the composites, and their UV and visible light photocatalytic activities were evaluated. Furthermore, the photocatalytic reaction mechanism was explored. Under solvothermal-calcination conditions (ethanol solvent, 700 °C, biomass/Zn mass ratio 0.30), the peanut-shell-derived ZnO/NOC composite delivered the highest combined adsorption and UV–vis photocatalytic activity. For instance, under UV light (300W Hg lamp), this ZnO/NOC composite achieved a degradation and decolorization rate of over 99.30% for the pollutant methylene blue (MB). Based on the ZnO/NOC composite, Cu and Sn were introduced to prepare two additional series of composites: Cu@ZnO/NOC and Sn@ZnO/NOC. The results indicated that under a calcination temperature of 700°C and a mass ratio of 0.30, the composites prepared with Cu-ZnO and Sn-ZnO molar ratios of 9.0% exhibited the best adsorption-photocatalytic performance. Comparing the three series (ZnO/NOC, Cu@ZnO/NOC, and Sn@ZnO/NOC), all demonstrated excellent adsorption and UV-visible light photocatalytic performance for pollutants. The performance was further improved due to the introduction of Cu and Sn, fully indicating that multi-component composition can effectively enhance material properties.